ҚАРАҚАЛПАҚ ТИЛИНДЕ ЖАНАПАЙЛАРДЫҢ АКСИОЛОГИЯЛЫҚ (БАҲАЛАЎШЫЛЫҚ) ХЫЗМЕТИ - Нзанова, С.К. (ILIM hám JÁMIYET, 2022)
The article considers the axiological function of particles in Karakalpak language. Also reveals the speaker’s evaluative attitude in speech.